Delta subfamily (version 2020.4) in the IUPHAR/BPS Guide to Pharmacology Database - Uddin, Mohib (IUPHAR/BPS Guide to Pharmacology CITE, 2020)
PKCδ and PKCθ are PKC isoforms that are activated by diacylglycerol and may be inhibited by calphostin C, Gö 6983 and chelerythrine.